Project Based Learning Method to Increase Students' Interest and Understanding in Learning Aqidah Akhlak at MTs Negeri 1 Magetan - Faqori, Yudha Bima; Mawati, Yelmi; Sulaeman, Wono; Suryani, Yani (MANDAILING GLOBAL EDUKASIA, 2024)
This classroom action research aims to increase students' interest and understanding of the material on Faith in the Apostles through the application of the Project Based Learning (PBL) model at MTsN 1 Magetan. The problems faced are the low involvement of students in the learning process and the lack of understanding of the concept of faith in the Apostles as a whole. This research was conducted in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The subjects of the study were students of class VIII MTsN 1 Magetan in the even semester of the 2024/2025 academic year. The instruments used included teacher and student activity observation sheets, learning interest questionnaires, and concept understanding tests. The results of the study showed that the application of the PBL model can increase student interest which is characterized by enthusiasm and active participation in project activities. In addition, there was a significant increase in student understanding test results from cycle I to cycle II. Based on these findings, it is concluded that project-based learning is effective in increasing students' interest and understanding of the material on Faith in the Apostles at MTsN 1 Magetan.